Integrating Religious Moderation in Islamic Education: A Narrative Review of Indonesia's Educational Strategies - Jamaluddin (Sinergi International Journal of Islamic Studies, 2024)
Religious moderation is increasingly recognized as a vital principle in Islamic education to counter radical ideologies and promote social harmony. This narrative review investigates how religious moderation is integrated into Islamic educational institutions in Indonesia, analyzing social, economic, educational, and policy-related factors that influence its implementation. Using a systematic literature review methodology, sources were retrieved from Scopus, Google Scholar, JSTOR, and Web of Science with a focus on peer-reviewed studies published between 2010 and 2024. Strategic keyword combinations and Boolean operators were employed to identify relevant literature. A total of 65 studies were selected based on defined inclusion and exclusion criteria, covering both empirical and conceptual research. Data from these studies were synthesized thematically across four categories—social, economic, educational, and policy dimensions—using a qualitative content analysis approach. Findings indicate that key social determinants, including interfaith dialogue, family influence, and institutional leadership, significantly shape students' attitudes towards moderation. Economic constraints often hinder curriculum development and teacher training, although financial support from government and NGOs proves effective. Educational attainment and religious literacy are positively correlated with openness to moderation, particularly when supported by culturally contextualized and interdisciplinary curricula. National and international policy frameworks offer substantial guidance, but inconsistent implementation and lack of localized strategies remain barriers. Comparative insights from countries such as Malaysia, Pakistan, Tunisia, and Turkey provide valuable models for policy adaptation. The review concludes that sustainable promotion of religious moderation in education requires coordinated policy, responsive curricula, robust teacher training, and community engagement. Future research should address underexplored dimensions such as student perspectives and the digital landscape. Overall, religious moderation must be positioned as a core value in education to nurture tolerant, critically-minded citizens.